Peer effects in parental leave decisions - Clara Welteke; Katharina Wrohlich (Labour Economics, 2019)
We analyze whether mothers' parental leave decisions depend on their coworkers' decisions. The identification of peer effects bears various challenges due to correlated characteristics within social groups. We therefore exploit quasi-random variation in the costs of parental leave induced by a policy reform in Germany. The reform encourages mothers to remain at home during the first year following childbirth. Administrative linked employer-employee data enable us to assign a peer group to individuals who work in the same establishment and occupation. Our results suggest that parental leave decisions are significantly influenced by coworkers' decisions.
Keywords: C31; J22; D04; 330; Peer effects; Social interaction; Labor supply; Family policy